2017
DOI: 10.18632/oncotarget.16920
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates acute paroxysmal sympathetic hyperactivity

Abstract: We evaluated the curative effect of dexmedetomidine on paroxysmal sympathetic hyperactivity (PSH) in a retrospective study of 72 PSH patients after neurosurgery. Our results showed that dexmedetomidine was superior to propofol for treatment of PSH with respect to: average time needed to reduce paroxysmal hypertension (PH) to <140/90 mmHg (29.03±8.86 vs. 42.0±14.77 min), average remission time of PH (3.97±1.73 vs. 5.65±1.51 min), PH remission rate (61.22±10.8% vs. 41.52±14.15%), PH duration (9.31±2.66 vs. 13.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
0
23
0
3
Order By: Relevance
“…In addition, dexmedetomidine has limited effects on respiratory drive and induces lighter sedation than comparative agents such as propofol or benzodiazepines. 26 Moreover, propranolol and dexmedetomidine both act systemically to modulate SNS outflow and reduce associated symptoms of PSH. 6,26 Concerns with using propranolol and dexmedetomidine in pediatric patients include bradycardia, hypotension, and decrease in CBF, however, these were not documented in our patient during treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dexmedetomidine has limited effects on respiratory drive and induces lighter sedation than comparative agents such as propofol or benzodiazepines. 26 Moreover, propranolol and dexmedetomidine both act systemically to modulate SNS outflow and reduce associated symptoms of PSH. 6,26 Concerns with using propranolol and dexmedetomidine in pediatric patients include bradycardia, hypotension, and decrease in CBF, however, these were not documented in our patient during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, propranolol and dexmedetomidine both act systemically to modulate SNS outflow and reduce associated symptoms of PSH. 6,26 Concerns with using propranolol and dexmedetomidine in pediatric patients include bradycardia, hypotension, and decrease in CBF, however, these were not documented in our patient during treatment. If any of these agents result in hemodynamic instability or compromise CBF in your patient, alternative agents should be chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine is available both in oral form and as a patch which makes its use even more practical. Dexmedetomidine, another presynaptic alpha 2 agonist, has been shown to be effective and in some reports even more effective than propofol in acute attacks [ 18 ]. Tang et al showed that dexmedetomidine can prevent the occurrence of PSH after TBI [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Следует отметить, что применение шкалы RASS во многом субъективно, и у ряда пациентов с низким уровнем сознания (вегетативный статус, минимальное сознание) не позволяет воспользоваться приведенными в ней клиническими критериями при подборе дозы дексмедетомидина. Эти и другие факторы побуждают к поиску объективных критериев, основанных на оценке многократно воспроизводимых физиологических параметров для применения данного лекарственного препарата [5,6]. Представ-…”
Section: Introductionunclassified